Effects of Carbon Fiber Reinforced Epoxy Composite Waste On Seed Germination and Seedling Growth of Plants - Zhu, Anping; Ci, Shengzong; Yu, Longjiang; Jiang, Huawei; Song, Linwei; Di, Chengrui; Qiao, Kun (Gesunde Pflanzen, 2024)
Carbon fiber reinforced polymer composites (CFRP), a new class of lightweight, high-performance materials, have seen a steady increase in usage over the years. This trend has concomitantly led to emergent challenges, including the disposal of CFRP waste, environmental pollution, and associated ecological impacts. To investigate the effects of CFRP waste on the germination and early growth stages of crops, rye and corn were selected as experimental subjects. Different waste contents, particle sizes, and soil distribution conditions were systematically established. The effects of CFRP waste on seed germination rates, plant height, stem diameter, and both fresh and dry weights, along with an assessment of soil nutrient content were comprehensively investigated. The findings indicate that CFRP waste markedly impedes both the germination process and the seedling development in rye and corn. With the increase in waste particle size and content, the germination rate, plant height, stem diameter, fresh weight, and dry weight of plants were inhibited. The maximum seed germination rate and dry weight decreased by less than 7% and more than 60% respectively in different groups. Moreover, finer waste particles and their integrated distribution were found to be particularly detrimental to plant growth. While the waste’s presence did not significantly alter soil nutrient profiles. The findings of this study provide a scientific foundation for future policy formulation on the management and disposal of emerging industrial waste, while also establishing a reference framework to assess the environmental impact posed by other forms of composite waste.